ANALISIS PENERAPAN SISTEM ENTERPRISE RESOURCE PLANNING (ERP) DALAM MENINGKATKAN KINERJA OPERASIONAL: (Study Kasus Di Perusahaan ERMYBAG) - Rini Muflihah; Eva Fauziah Nur Cholisoh (LPPM IAIT, 2025)
This study aims to analyze how the implementation of ERP systems by retail companies Ermybag can affect the improvement of operational performance. This research uses a descriptive qualitative method with a case study approach, through in-depth interviews, direct observations, and documentation related to operational activities at Ermybag. The results of the study show that the implementation of the ERP system at ermybag in general has a positive impact on operational performance. Work processes that were previously carried out manually and separately are now more integrated, and documented in real time. ERP allows information between divisions to be accessed more easily, speeds up decision-making, and reduces data duplication. However, significant challenges were also found in terms of data quality and stock accuracy due to the absence of standard operating procedures (SOPs) and low data input discipline by users. This study provides an important implication that the success of ERP implementation does not only depend on the technological system, but also on management readiness, work culture, and strengthening internal operational procedures. By designing clear SOPs and increasing the capacity of HR in the use of the system, companies can maximize the potential of ERP in improving operational performance. This research is expected to be a reference for other retail companies to adopt ERP systems, as well as a theoretical contribution to the development of management information system studies.